Analysis Of Student Satisfaction Level In The Faculty Of Science And Technology Using The Convolution Neural Network Method - Martua , Rifki Agus; Irmayani , Deci; Yanris, Gomal Juni (International Journal of Science, Technology & Management, 2024)
The Faculty of Science and Technology at Labuhanbatu University is one of the leading faculties that focuses on the development of science and technology. This faculty offers various study programs designed to prepare students to face the challenges of the digital era and industrial revolution 4.0. This research, using survey and interview methods, aims to collect accurate and objective data regarding student perceptions and experiences in various aspects, such as the quality of educational services, quality of teaching, and available supporting facilities such as extracurricular activities, seminars and research projects, ease of access. information and academic support from optimal staff and teaching staff.